Building Bridges and Widening Gaps: Wage Gains and Equity Concerns of Labor Market Expansions - Aline Bütikofer; Katrine Vellesen Loken; Alexander Willén (Institute of Labor Economics (IZA), 2020)
We exploit the construction of the Öresund bridge, which connects a medium-sized city in Sweden to the capital of Denmark, to study the labor market effects of gaining access to a larger labor market. Using unique cross-country matched registry data that allow us to follow individuals across the border, we find that the bridge led to a substantial increase in cross-country commuting among Swedish residents. This effect is driven both by extensive and intensive margin employment responses, and translates into a 15% increase in the average wage of Swedish residents. However, the wage effects are unevenly distributed: the effect is largest for high-educated men and smallest for low-educated women. Thus, the wage gains come at the cost of increased income inequality and a widening of the gender wage gap, both within- and across-households. We show that these inequality effects are driven not only by differences in the propensity to commute, but also by educational specialization.
Keywords: J3; J61; 330; labor market expansions; wages; distributional consequences